2020
DOI: 10.1111/1753-6405.12954
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and fast food sponsorship in sporting clubs with junior teams participating in the ‘Good Sports’ program: a cross‐sectional study

Abstract: Objective: To examine: alcohol and fast food sponsorship of junior community sporting clubs; the association between sponsorship and club characteristics; and parent and club representative attitudes toward sponsorship. Methods: A cross‐sectional telephone survey of representatives from junior community football clubs across New South Wales and Victoria, Australia, and parents/carers of junior club members. Participants were from junior teams with Level 3 accreditation in the ‘Good Sports’ program. Results: A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…We also found that the odds of being affiliated with an unhealthy food and high-risk food sponsor were 2-3 fold greater for clubs located in regional compared with metro areas (no significant difference for alcohol and gambling sponsorship). These findings concur with those of Gonzalez et al who found that sporting clubs located in regional areas are more likely to be sponsored by fast-food companies compared with clubs located in metropolitan areas (25) . It is plausible that the regional difference relates to the greater number of all food sponsors (healthy and unhealthy) in regional areas, reflecting a greater reliance on sponsorship to cover operating costs of the club.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…We also found that the odds of being affiliated with an unhealthy food and high-risk food sponsor were 2-3 fold greater for clubs located in regional compared with metro areas (no significant difference for alcohol and gambling sponsorship). These findings concur with those of Gonzalez et al who found that sporting clubs located in regional areas are more likely to be sponsored by fast-food companies compared with clubs located in metropolitan areas (25) . It is plausible that the regional difference relates to the greater number of all food sponsors (healthy and unhealthy) in regional areas, reflecting a greater reliance on sponsorship to cover operating costs of the club.…”
Section: Discussionsupporting
confidence: 92%
“…However, our findings are in accordance with a recent study by Gonzalez et al, which examined sponsorship arrangements across seventy-nine junior community sporting clubs (covering Australian rules football (AFL) and rugby league) in the Australian states of New South Wales and Victoria participating in the 'Good Sports Program'. Similar to our findings, the study found a high proportion of clubs were affiliated with an alcohol or fast-food company, with half the clubs sponsored by the alcohol industry and a quarter sponsored by fast-food companies (25) .…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations